Dampak Penumpukan Dokumen Rekam Medis Terhadap Waktu Pengambilan Dokumen Rekam Medis Di RSU Sinar Husni Medan - Valentina; Selvia Sari Ritonga (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda, 2021)
The filling system is one of the administrators of medical records which is responsible for orderly administration in an effort to improve health services in hospitals. Accumulation of medical record documents will affect of work of officers in the filling section. The purpose of this study is to determine the impact of the bildup of medical records documents on the time of taking medical record documents at Sinar Husni Hospital. This research is a descriptive study with a qualitative approach. The population is all filling officers at the Sinar Husni Hospital and all patient medical records calculated on average in the third quarter of 2020, counted 719 documents. The samples in this study were 2 filling officers at the Sinar Husni Hospital and part of the medical record documents totaling 86 medical record documents that were taken incidentally. The instrument used was an interview guide. The measurement of time to take medical record documents uses a stopwatch. Data were analyzed descriptively. The results showed that the accumulation of medical record documents had an impact on the time to take medical record documents at the Sinar Husni Hospital, because the officers had difficulty carrying out filling activities because the access between shelves was narrower and the documents piled on the floor were not properly aligned, with an average of 10.05 minute. We recommend to add more storage space and shelves so that medical record documents that are stacked on the floor can be moved to the storage racks.